Basic chemistry - Zumdahl, Steven S.; DeCoste, Donald J. (Brooks/Cole, Cengage Learning, 2011)
This Seventh Edition of Zumdahl/DeCoste's best-selling INTRODUCTORY CHEMISTRY: A FOUNDATION extends its focus on conceptual learning and problem solving to provide readers with the tools they need to become critical thinkers and problem solvers